Code-Mixing Used by SP and AY in WhatsApp Chats - Jusuf Sharon; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This study examines the use of code-mixing between SP and AY in WhatsApp chats. Muysken’s (2000) theory of code-mixing is used as the main framework, and Holmes’ (2013) theory of social factors serves as the supporting theory. A qualitative method is employed, with basic frequency counts. The study revealed that SP and AY used all three types of code-mixing, namely insertion, alternation, and congruent lexicalization. All four indicators namely, constituency, switch site, element switched, and properties were applied by both speakers with differences. This study also discusses how participant roles and communicative functions influence their code-mixing practices.